Post-facelift flap necrosis treatment using charged polystyrene microspheres. Issue 1 (March 2013) - Weissman, Oren; Farber, Nimrod; Remer, Eric; Tessone, Ariel; Trivizki, Omer; Bank, Jonathan; Winkler, Eyal; Zilinsky, Isaac; Haik, Josef
Background: Flap necrosis following facial rhytidectomy constitutes a vexing and grievous complication to the patient and the surgeon. Treatment modalities that can expedite wound healing and re-epithelialization rates are highly desired. Objectives: To assess wound healing and re-epithelialization rates of open wounds following postrhytidectomy flap necrosis treated with commercially available charged polystyrene microspheres (Polyheal-1, Polyheal Ltd, Israel). Methods: Flap necrosis following rhytidectomy with open wounds in three female patients were treated using dressings soaked with Polyheal-1. Wound closure rates were documented. Results: The wounds demonstrated both accelerated granulation tissue formation and rapid re-epithelialization rates. No complications or side effects were encountered. Conclusions: Charged polystyrene microspheres may offer a new and efficacious way to treat open wounds due to flap necrosis following facial rhytidectomy. Further research with larger patient numbers is still needed to verify these findings.